Masterpieces of the Avantgarde : Three Decades of contemporary Art : The Sixties, The Seventies, The Eighties, Twenty Five Years Annely Juda Fine Art - Juda Rowan Gallery. - Januszczak, Waldemar; Lynton, Norbert; Robertson, Bryan; Vaizey, Marina; Annely Juda Fine Art, London; Juda Rowan Gallery, London (London : Annely Juda Fine Art, 1985)
Arp, Hans (Jean) ; Ascott, Roy ; Atkin, John ; Ayres, Gillian ; Balthus ; Bergmann-Michel, Ella ; Brazdys, Antanas ; Chalk, Martyn ; Chandra, Avinash ; Christo ; Cohen, Bernard ; Craig-Martin, Michael ; Davies, John ; Denny, Robyn ; Domela, César ; Donaldson, Anthony ; Edwards, John ; Evans, Garth ; Flanagan, Barry ; Friedeberger, Klaus ; Georgiadis, Nicholas ; Giacometti, Alberto ; Golding, John ; Gontcharova, Natalie ; Gorin, Jean ; Green, Alan ; Green, Anthony ; Green, June ; Hall, Nigel ; Haraguchi, Noriyuki ; Hawkes, Julian ; Honegger, Gottfried ; Hughes, Malcolm ; Huszar, Vilmos ; Huxley, Paul ; Kalkhof, Peter ; Kenny, Michael ; Kidd, Richard ; King, Phillip ; Klee, Paul ; Kliun, Ivan ; Klucis, Gustav ; Lancaster, Mark ; Laurens, Henri ; Leapman, Edwina ; Leger, Fernand ; Lissitzky, El ; Malevich, Kasimir ; McLaughlin, John ; Meyrick, George ; Michaeledes, Michael ; Michel, Robert ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Moon, Jeremy ; Moore, Henry ; Morellet, François ; Nash, David ; Naylor, Martin ; Picasso, Pablo ; Popova, Liubov ; Reynolds, Alan ; Riley, Bridget ; Rodchenko, Alexander ; Saito, Yoshishige ; Schwitters, Kurt ; Scott, Patrick ; Scully, Sean ; Smith, Keir ; Tajiri, Shinkichi ; Tatlin, Vladimir ; Toren, Amikam ; Tucker, William ; Turnbull, William ; Underhill, Tony ; Vantongerloo, Georges ; Vordemberge-Gildewart, Friedrich ; Warhol, Andy ; Werner, Michael ; Werthmann, Friedrich ; Young, Brian
biog. per kunstenaar
Engels
Three Decades of Contemporary Art : The Sixties, 17 September - 19 October, 1985 ; The Seventies, 22 October - 23 November, 1985, The Eighties, 26 November - 20 December, 1985
boek